A Longitudinal Study to Assess the Impact of Psychiatry Clinical Rotation Program on Attitude Towards Mental Illness Among Intern Doctors - Smrity Shailly Bagde; Romesh Bagde; Sushil Gawande; Yash Vaghani; Sudhir Bhave; Vivek Kirpekar; Rahul Tadke (Journal of Psychiatry Spectrum, 2025)
Background: Attitude of medical students and intern doctors toward mental illness is of great importance. They are likely to encounter and care for these patients as doctors. Previous studies observed that 68% of the students felt persons with mental illness (PMI) should not be treated with other patients. Seventy percent of students agreed on the disrespectful attitude of other staff toward PMI. Studies also noticed a significant change in attitude toward mental illness after undergoing psychiatry training programs. Aims and Objectives: The aims and objectives of this study were to assess the attitude of intern doctors toward mental illness and to study the impact of the psychiatry clinical rotation program on their attitude. Materials and Methods: This prospective and interventional study was carried out in a tertiary care hospital for 10–12 months. Institutional ethics committee approval was taken, a total of 132 doctors were selected, and attitude toward mental illness scale was applied on baseline and after completion of clinical rotation. Results: Attitude toward mental illness score on baseline was 111.32 ± 5.15 and after completion of rotation program was 104.61 ± 4.44. Significant improvement was noted post completion of the clinical rotation program (P < 0.001). Conclusion: Thus, complete holistic training increased their awareness about mental illness. It also helped in building empathy toward PMI. Innovative learning and teaching methods played a key role in enhancing their scientific knowledge about psychiatric illness and its treatment. Hence, this program was beneficial in changing their attitude and perception toward psychiatric illness.